María Buschental: A salonnière in Madrid - IRENE MENDOZA MARTÍN; FERNANDO MOYA BERLANGA (Estudios de Historia de España, 2021)
María Buschental (1815-1891) has been scarcely researched, which is surprising because she was a prominent member of Madrid's daily life because for many years she organized an important salon. The organization of her soirées, which preserved the characteristics of these since its hatching in France, for over 40 years was what allowed her to overcome some limits that were associated with her gender. In this article, we reconstruct her biography and analyze the dynamics that were established in her soirées over time. Thanks to her idiosyncrasy, our protagonist managed to turn her salon into a place on the border between public and private space, which allowed her to participate indirectly in the politics of her time.